A new genus, new species and taxonomic notes on American Cerambycinae (Coleoptera, Cerambycidae) - Botero, Juan Pablo; Bezark, Larry G.; Santos-Silva, Antonio (Zootaxa, 2020)
Four new species and one new genus are described: Nesanoplium spinosum (Elaphidiini), from Honduras; Psyrassa zacki (Elaphidiini), from Mexico and Guatemala; Euderces ecuadorensis (Tillomorphini), from Ecuador; and Xela tysoni (Methiini), gen. nov., from Guatemala. Pteroplatus suturalis Buquet, 1840 is synonymized with Pteroplatus pulcher Buquet, 1840 (Pteroplatini). Acyphoderes baeri Gounelle, 1913 (= Odontocera baeri) is transferred to Acutiphoderes Clarke, 2015 (Rhinotragini). We question the validity of the lectotype designation for Cyrtomerus puberulus Fleutiaux & Sallé, 1889.